Reversible ammonia uptake at room temperature in a robust and tunable metal–organic framework. Issue 13 (8th March 2022) - Lee, Jaechul; Seo, Younggyu; Kang, Dong Won; Park, Seungjae; Kim, Hyunyong; Kim, Jaheon; Kim, Kimoon; Hong, Chang Seop; Lim, Dae-Woon; Lee, Eunsung
Abstract : Recyclable and tunable ammonia adsorption with JCM-1 and JCM-1(Cl − ) at room temperature occurs reversibly without structural decomposition. Abstract : Ammonia is useful for the production of fertilizers and chemicals for modern technology, but its high toxicity and corrosiveness are harmful to the environment and human health. Here, we report the recyclable and tunable ammonia adsorption using a robust imidazolium-based MOF (JCM-1 ) that uptakes 5.7 mmol g −1 of NH3 at 298 K reversibly without structural deformation. Furthermore, a simple substitution of NO3 − with Cl − in a post-synthetic manner leads to an increase in the NH3 uptake capacity of JCM-1(Cl − ) up to 7.2 mmol g −1 .